Production of compressed stabilized earth block (CSEB) from Pulangui reservoir alluvial sediments using coal fly ash as partial replacement to cement as binder - Opiso, Einstine M. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
Siltation at Pulangui Reservoir in Maramag, Bukidnon is a big problem for the hydroelectric power plant. This study explores the potential of Pulangui alluvial sediments from five different locations for compressed stabilized earth block (CSEB) production based on the soil consistency and textural properties of sediments and compressive strength of the blocks. the effect of coal fly ash as partial replacement to ordinary portland cement as binder was also examined. The results showed that the soil consistency and textural properties of alluvial sediments failed to pass the suitability criteria for CSEB. Additional sand was added in1:2 ratio (soil to sand). The replacement of cement with coal fly ash tends to increase its compressive strength up to 20% replacement of cement. The highest compressive strength was observed from the alluvial soils of Panadtalan with 4.32 a . CSEB is viewed to have certain potentials that have the comparative advantage over other materials like hollow blocks but needs a promotional campaign to encourage its usage. The comparative cost analysis revealed that the CSEB with coal fly ash is only 4.30% cheaper compared to the conventional method. Overall, the alluvial deposits of Pulangui reservoir and coal fly ash could be utilized for CSEB production.